(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This thesis investigates the morphological and semantic characteristics of acronyms in English and Uzbek languages. Acronyms play a crucial role in modern communication by shortening long expressions and increasing efficiency. The study examines their formation, pronunciation, grammatical behavior, and semantic development. It also highlights how acronyms function in different communicative contexts such as education, media, and technology. The research demonstrates both similarities and differences between the two languages and emphasizes the importance of acronyms in linguistic studies.